2012
DOI: 10.1136/bmjspcare-2011-000063
|View full text |Cite
|
Sign up to set email alerts
|

Continuous palliative sedation until death: practice after introduction of the Dutch national guideline

Abstract: Continuous palliative sedation practice in The Netherlands largely reflects the recommendations from the national guideline. Issues needing further attention are the pressure felt by physicians to start continuous sedation and the potential life-shortening effect as mentioned by the physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…This suggests one PSa consultation by PCC teams for every 15 cases of palliative sedation in the Netherlands (12.3%/0.8%). This rate is lower than the consultation rate of 22% found by Swart et al[ 24 ] One explanation for this different consultation rate, could be that Swart et al asked physicians whether they consulted any palliative care team, whereas we only studied consultations requested at PCC teams. Anyhow, our finding demonstrates that the use of PCC teams for palliative sedation seems not a common practice.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…This suggests one PSa consultation by PCC teams for every 15 cases of palliative sedation in the Netherlands (12.3%/0.8%). This rate is lower than the consultation rate of 22% found by Swart et al[ 24 ] One explanation for this different consultation rate, could be that Swart et al asked physicians whether they consulted any palliative care team, whereas we only studied consultations requested at PCC teams. Anyhow, our finding demonstrates that the use of PCC teams for palliative sedation seems not a common practice.…”
Section: Discussioncontrasting
confidence: 59%
“…[ 36 , 37 ] The finding that exhaustion is associated with a higher likelihood of PSa consultations is in line with other research conducted in the Netherlands, stating that exhaustion is a common indication to start palliative sedation. [ 20 , 24 ] However, it is not mentioned as a common indication for palliative sedation in recent international literature. [ 35 ] Furthermore, although pain is a commonly mentioned symptom during PSa consultations (2,924 PSa consultations; 36.4%), resonating with the literature,[ 20 , 24 , 25 ] it is not independently associated with a higher likelihood of PSa consultations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few quantitative studies have addressed the issue of using sedation for the relief of psychological and existential suffering of severely ill patients. According to Dutch physicians, existential suffering, anxiety, and depression were amongst the indications for sedation mentioned for respectively 29%, 13%, and 30% of the patients 14 . British physicians reported that in 25% of the cases in which their patient had been continuously and deeply sedated, sedation had been given because of the patient's intractable psychological suffering (whether or not in combination with other reasons) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…A secondary analysis was performed of data that were collected among physicians in a study that evaluated the practice of palliative sedation after the introduction of the Royal Dutch Medical Association guideline 13 14. Data collection took place between February 2008 and September 2008.…”
Section: Methodsmentioning
confidence: 99%